Erdös Type Inequality for Lorentz Polynomials (Analysis in Theory and Applications, 2018)
An elementary, but very useful tool for proving inequalities for polynomialswith restricted zeros is the Bernstein or Lorentz representation of polynomials. In thepresent paper, we give two classes of Lorentz polynomials, for which the Erd\u00f6s-type inequality holds.
Keywords: Lorentz representation of polynomials; constrained polynomials; Morkov-type inequalities; Erdös-type inequality.